Free Tropospheric Aerosol Measurements at the Pico Mountain Observatory, Azores (2225m asl). - Mazzoleni, Claudio (2012)
In this poster we discuss a limited subset of the aerosol measurements performed at the Pico Mountain Observatory. The Black Carbon (BC) mass shows a clear seasonal pattern over a ten-years period. The 2012 scattering measurements show highly variable signals with events with high scattering and periods of very low aerosol loading. Dust events are clearly captured by the aethalometer, as well the nephelometer Ångström exponents. Particles have various shapes, and mixing states, and soot particles typically are very compacted.